1998
DOI: 10.1074/jbc.273.41.26820
|View full text |Cite
|
Sign up to set email alerts
|

Light-dependent Activation of Rod Transducin by Pineal Opsin

Abstract: The pineal gland expresses a unique member of the opsin family (P-opsin; Max, M., McKinnon, P. J., Seidenman, K. J., Barrett, R. K., Applebury, M. L., Takahashi, J. S., and Margolskee, R. F. (1995) Science 267, 1502-1506) that may play a role in circadian entrainment and photo-regulation of melatonin synthesis. To study the function of this protein, an epitope-tagged P-opsin was stably expressed in an embryonic chicken pineal cell line. When incubated with 11-cis-retinal, a light-sensitive pigment was formed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…A number of unique genes that are expressed in these cells do not appear to be expressed in other tissue. In addition to SPACRCAN (Wang et al, 1996;Acharya et al, 2000), retinal photoreceptors and pinealocytes also synthesize interstitial retinol-binding protein (IRBP; Rodrigues et al, 1986), cone arrestin (Craft et al, 1994), opsins (Vigh et al, 1998), transducin (Max et al, 1998), and several other proteins involved in the phototransduction cascade (Blackshaw and Snyder, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…A number of unique genes that are expressed in these cells do not appear to be expressed in other tissue. In addition to SPACRCAN (Wang et al, 1996;Acharya et al, 2000), retinal photoreceptors and pinealocytes also synthesize interstitial retinol-binding protein (IRBP; Rodrigues et al, 1986), cone arrestin (Craft et al, 1994), opsins (Vigh et al, 1998), transducin (Max et al, 1998), and several other proteins involved in the phototransduction cascade (Blackshaw and Snyder, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…This opsin possesses the characteristic features of a visual opsin (equivalents of Lys-296, Glu-113, Cys-110 and Cys-187, and Asn-15), but its expression is restricted to the pineal and thus was named pinopsin. In vitro expression of chicken pinopsin and its reconstitution with 11-cis-retinal reveals that this opsin possesses a maximal absorbance (λ max ) of 470 nm (Nakamura et al 1999;Okano et al 1994) and 462 nm (Max et al 1998). Max et al (1995) confirmed the localisation of chicken pinopsin to the pineal and determined the structure of the gene.…”
Section: P-opsinmentioning
confidence: 98%
“…Light-dependent activation of bovine transducin by using filter binding assays were carried out as described (16,18).…”
Section: Methodsmentioning
confidence: 99%